PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY BERBANTUAN MEDIA KARTU SOAL TERHADAP LITERASI BACA TULIS SISWA DI UPTD SD NEGERI 28 PAREPARE - Nurul Mukhlisa; Nur Ilmi; Zulfahira, Zulfahira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine whether or not there is an influence of the course review horay learning model assisted by question card media on students' reading and writing literacy at UPTD SD Negeri 28 Parepare. The approach used in this research is a quantitative approach with a Quasi Experimental research design in the form of a Nonequivalent Control Group Design. The population in this study was all 375 UPTD students at SD Negeri 28 Parepare, while the sample was class IV.1 as the control class and class IV.2 as the experimental class. The data collection technique used is a test in the form of multiple choice and description. The data analysis technique used is descriptive statistics and inferential analysis techniques with the Independent Sample T-test. Based on the results of inferential statistical analysis, it shows Sig (2 - tailed) = 0.011 < 0.05, so H0 is rejected and H1 is accepted. Thus, the conclusion of this research is that the course review horay learning model assisted by question card media has an effect on increasing students' reading and writing literacy at UPTD SD Negeri 28 Parepare.